(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This scientific article provides an in-depth review and original analysis of construction technologies for hydraulic barriers used in the stabilization of riverbanks, with a focus on their design, engineering principles, materials, implementation techniques, and long-term performance under diverse hydrological and environmental conditions. Integrating international scientific literature, case studies from river engineering projects in Central Asia, Europe, North America, and advanced materials research, the article examines the evolution of riverbank stabilization practices—from traditional hard structural solutions such as riprap, retaining walls, and sheet piling to modern integrated approaches that combine green infrastructure, bioengineering, and digital monitoring technologies. The review details the mechanisms of riverbank erosion, factors influencing the selection and design of hydraulic barriers, and the comparative performance of different construction materials and methods. The article synthesizes quantitative and qualitative assessments of barrier effectiveness, construction challenges, maintenance requirements, and environmental impacts, providing robust recommendations for sustainable, resilient riverbank stabilization that supports both engineering and ecological objectives. The review concludes with a discussion of future research priorities and policy directions for riverbank protection in Uzbekistan and other riverine regions exposed to climate variability and anthropogenic pressures.